Impact of COVID-19 pandemic on the neurosurgical practice in Egypt - Mohamed Nabil; Mohammed Dorrah; Asmaa Sharfeldin; Hassan Abaza (Egyptian Journal of Neurosurgery, 2022)
Abstract Background The COVID-19 pandemic and the subsequent lockdown have significantly altered many aspects of the health care services. We investigated the impact of the restrictive measures during the pandemic on the volume and spectrum of operated neurosurgical cases at two University hospitals in Egypt. Results The total number of surgeries dropped during the lockdown (second quarter of the year 2020) by 38%, compared with the total number of surgeries in the first quarter of the same year, with an increase in the proportion of urgent surgeries to the total number of surgeries from 46 to 69% (P < 0.001), and a decrease in the proportion of elective surgeries from the total number of neurosurgeries from 54 to 31% (P < 0.001). Similar differences were noted in the volume and spectrum of surgeries in the second quarter of 2020, when compared to the same period of the preceding year (2019). Conclusions The COVID-19 pandemic has significantly altered the nature and volume of neurosurgical practice. The overall number of surgeries showed a marked decline in the lockdown period; however, the numbers of urgent surgeries showed no significant difference under the lockdown.